Kajian Antropologi, Semiotika, Estetika Dan Pendidikan Karakter Dalam Permainan Tradisional Kul Kuk - Degus Jaya, I Wayan (Metta : Jurnal Ilmu Multidisiplin, 2021)
Traditional games, especially traditional Balinese games, are starting to be abandoned, one of the reasons is the rapid development of technology in various aspects of life, one of which is digital games. This is a problem which, if prolonged, will actually lead to the extinction of traditional games. In this research traditional games Kul Kuk analyzed in several scientific disciplines, namely, anthropology, semiotics and aesthetics. The aim of this research is to analyze traditional games Kul Kuk in anthropology, semiotics and aesthetic studies. The method used in this research is descriptive qualitative. By using this method, various meanings or messages in traditional games can be analyzed and described Kul Kuk.The results of this research show that in anthropological studies, traditional games can be studied from a cultural and social perspective. Semiotic studies can help in understanding the meaning and values ​​of the characters contained in traditional games which are then interpreted through semiotic analysis to reveal the character values ​​contained in traditional games. Aesthetic aspects in traditional games Kul Kuk namely found in several body movement patterns such as running upright, bending down and creeping. The aesthetic aspect of this game is also found in the accompanying music and traditional game songsKul Kuk. Meanwhile, the value of character education in traditional games Kul Kuk (1) religious; (2) nationalist; (3) independent; (4) mutual cooperation; (5) integrity. Interdisciplinary research in traditional games Kul Kuk gain understandingdeeper into the social, cultural, semiotic and aesthetic aspects related to the game Whichhelps us appreciate traditional gamesKul Kuk as part of cultural heritage.